2002
DOI: 10.1007/s00125-001-0749-6
|View full text |Cite
|
Sign up to set email alerts
|

Islet autoantibodies, nationality and gender: a multinational screening study in first-degree relatives of patients with Type I diabetes

Abstract: Relatives from different European countries have similar rates of islet autoimmunity despite wide variation in the background incidence of childhood diabetes, and male excess is equally evident in all populations. The male excess of ICA and islet autoimmunity over 10 years of age reflects the higher male incidence of Type I diabetes in this age group, and suggests that boys may be more likely than girls to develop islet autoimmunity during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
20
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 18 publications
(21 reference statements)
5
20
0
Order By: Relevance
“…Error bars represent SE sembling that of early childhood, while adolescent females tend to have a more adult profile, with higher GAD antibody levels. A similar excess of IAA was observed in male relatives of patients with Type 1 diabetes over the age of 10 in a recent screening study [2]. These observations would be consistent with continued expansion of islet autoimmunity in adolescent males and/or down-regulation of islet autoimmunity in females with puberty.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Error bars represent SE sembling that of early childhood, while adolescent females tend to have a more adult profile, with higher GAD antibody levels. A similar excess of IAA was observed in male relatives of patients with Type 1 diabetes over the age of 10 in a recent screening study [2]. These observations would be consistent with continued expansion of islet autoimmunity in adolescent males and/or down-regulation of islet autoimmunity in females with puberty.…”
Section: Discussionsupporting
confidence: 82%
“…The lower prevalence of IAA in adolescent females implies sex-specific modulation of the autoimmune process during puberty. [Diabetologia (2003) In a recent multinational screening study of firstdegree relatives, we found a higher prevalence of islet autoimmunity in males than females during adolescence [2]. Strikingly, the prevalence of IAA did not vary up to 20 years of age in islet cell antibody (ICA) positive male relatives, whereas in female relatives the prevalence fell sharply between the ages of 10 and 20 years.…”
mentioning
confidence: 79%
“…Not all individuals that carry autoantibodies towards the beta cells ultimately develop clinical diabetes, and the signs of autoimmunity may disappear [11][12][13]. Autoantibody prevalence is similar among relatives of type 1 diabetic patients in different countries, despite a wide variation in diabetes incidence [14]. Many authors thus agree that, once autoimmunity has been triggered, the progressive decrease in beta cell function may be caused by subsequent exposure events [7,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…ICA determination in the central laboratory was performed by indirect immunofluorescence [7]. Briefly, sera were incubated on sections of human pancreas for 30 min at room temperature.…”
Section: Islet Cell Antibodiesmentioning
confidence: 99%